Analyzing the Implications of Living Law in the Draft Criminal Law Substance Based on Case Studies of Indigenous Peoples in Indonesia - Zulianty, Renita; Kurniawan, Andre (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In carrying out policies to formalize customary law in the RKUHP it is not a solution in an essential settlement to humanize citizens in indigenous peoples. But especially in an effort to provide mapping and identification of social substance with adat that is rolling in Indonesia and it is not an easy matter to identify identities within indigenous peoples and their laws are also not single and uniform in developments and changes in law and there are people who cannot be detained. The purpose of this research article is the implications of living law on the draft criminal law substance based on case studies of indigenous peoples in Indonesia. So the results and research can be obtained. Law enforcement institutions in the criminal justice system have responded very well to the practices of peaceful resolution mechanisms in criminal cases such as forgiveness and peace agreements that often occur in society. These institutions, namely the Indonesian National Police, the Attorney General's Office of the Republic of Indonesia, and the Supreme Court of the Republic of Indonesia have accommodated the mechanism for peace between victims and perpetrators with a restorative justice approach, namely formulated in the internal regulations of each institution.